2013
DOI: 10.4161/auto.23066
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of nutrient-sensitive autophagy by uncoordinated 51-like kinases 1 and 2

Abstract: Macroautophagy, commonly referred to as autophagy, is a protein degradation pathway that occurs constitutively in cells, but can also be induced by stressors such as nutrient starvation or protein aggregation. Autophagy has been implicated in multiple disease mechanisms including neurodegeneration and cancer, with both tumor suppressive and oncogenic roles. Uncoordinated 51-like kinase 1 (ULK1) is a critical autophagy protein near the apex of the hierarchal regulatory pathway that receives signals from the mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
135
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(150 citation statements)
references
References 48 publications
(87 reference statements)
13
135
1
1
Order By: Relevance
“…18,19 Using siRNA-mediated knockdown of genes encoding ULK complex components including ULK1, ATG13 and RB1CC1 as well as siRNA-targeting the gene for the autophagy receptor protein SQSTM1, we confirmed that all 3 ULK complex components have a comparable effect on basal autophagic flux (Fig. 6A, Fig.…”
Section: Ulk1 Is Required For Basal Autophagy and Autophagic Flux Undsupporting
confidence: 50%
“…18,19 Using siRNA-mediated knockdown of genes encoding ULK complex components including ULK1, ATG13 and RB1CC1 as well as siRNA-targeting the gene for the autophagy receptor protein SQSTM1, we confirmed that all 3 ULK complex components have a comparable effect on basal autophagic flux (Fig. 6A, Fig.…”
Section: Ulk1 Is Required For Basal Autophagy and Autophagic Flux Undsupporting
confidence: 50%
“…Accordingly, although WIPI1 localization at autophagosomal membranes is ablated upon Ca 2+ chelation, WIPI1-positive autophagosomes are formed in AMPK-deficient mouse embryonic fibroblasts, probably involving an AMPK-independent route through CAMKI (Pfisterer et al, 2011). It is noteworthy that the PtdIns3P effector function of WIPI1 does not respond to glucose starvation (McAlpine et al, 2013;Pfisterer et al, 2011), which generally activates AMPK. Glucose starvation has been suggested to signal independently of PtdIns3P to trigger autophagy (McAlpine et al, 2013).…”
Section: Wipi1mentioning
confidence: 97%
“…It has been demonstrated that mTORC1 inhibition, either by rapamycin administration (Proikas-Cezanne et al, 2007), siRNAmediated mTOR downregulation (Gaugel et al, 2012) or FOXOmediated glutamine production (van der Vos et al, 2012), promotes the localization of WIPI1 at the nascent autophagosome. This specific localization of WIPI1 is counteracted by the downregulation of ULK1 or PI3KC3 (Itakura and Mizushima, 2010;McAlpine et al, 2013). Hence, the activation of ULK1 and PI3KC3, followed by localized PtdIns3P production, rapidly attracts WIPI1 through its PtdIns3P-binding specificity.…”
Section: Wipi1mentioning
confidence: 99%
See 1 more Smart Citation
“…AMPK␣1 Ϫ/Ϫ AMPK␣2 Ϫ/Ϫ MEFs, which lack both isoforms of the genes that encode the catalytic ␣-subunit of AMPK, have been described previously and were kindly provided by Dr. Sara Cherry (U. Pennsylvania) (42,43). ULK1 ϩ/ϩ , ULK1 Ϫ/Ϫ , and ULK1 Ϫ/Ϫ ULK2 Ϫ/Ϫ MEFs were kindly provided by Dr. Sharon Tooze (44). MEFs were routinely cultured in DMEM containing 5% FBS.…”
Section: Primary Macrophage Isolation and In Vitro Cell Culture-mentioning
confidence: 99%